An exploration of school mobility: Risks and protective factors in late elementary. Issue 12 (15th May 2020) - Dinnen, Hannah L.; Baker, Jack; Dallal, Renee; Brann, Kristy; Flaspohler, Paul D.
Abstract: This study explored negative emotional, behavioral, and academic performance outcomes for highly mobile students and potential protective factors. Participants were fourth and fifth‐grade students ( N  = 647, 51% male) from three schools with low socioeconomic status, highly mobile student populations within a large, suburban school district in the midwestern United States. Data were collected through student self‐report surveys, teacher‐report surveys, and school records. Multilevel moderation analysis tested whether school connectedness (SC) or social and emotional competence (SEC) acted as protective factors for highly mobile students, moderating the effect of school mobility on emotional problems and academic performance. Student mobility was associated with more emotional problems and lower academic performance. In contrast to past research, there was not an association between mobility and behavior problems. Although they did not act as protective factors, SC and SEC were independently associated with fewer emotional problems and stronger reading performance for all students, controlling for mobility. Results build on existing evidence that student mobility has negative effects on emotional and academic outcomes and lend support for interventions focused on enhancing SC and SEC of all students, including those at increased risk due to high mobility.